2022
DOI: 10.1186/s40246-022-00411-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ACE2 naturally occurring missense variants: impact on subcellular localization and trafficking

Abstract: Background Human angiotensin-converting enzyme 2 (ACE2), a type I transmembrane receptor physiologically acting as a carboxypeptidase enzyme within the renin-angiotensin system (RAS), is a critical mediator of infection by several severe acute respiratory syndrome (SARS) corona viruses. For instance, it has been demonstrated that ACE2 is the primary receptor for the SARS-CoV-2 entry to many human cells through binding to the viral spike S protein. Consequently, genetic variability in ACE2 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Consistently, this variant has been previously classified as a benign variant using various in silico analysis tools including SIFT, MUTTASTER, PROVEAN, PolyPhen-2, CADD, and REVEL [24,31,32]. Other studies, based on structural modeling and molecular docking simulations suggested that the p.Lys26Arg increased binding affinity of SARS-CoV-2 spike protein to the ACE2 receptor and showed increased SARS-CoV-2 infection as compared to the wildtype ACE2 [9,14,24,26,33,34].…”
Section: Discussionmentioning
confidence: 65%
“…Consistently, this variant has been previously classified as a benign variant using various in silico analysis tools including SIFT, MUTTASTER, PROVEAN, PolyPhen-2, CADD, and REVEL [24,31,32]. Other studies, based on structural modeling and molecular docking simulations suggested that the p.Lys26Arg increased binding affinity of SARS-CoV-2 spike protein to the ACE2 receptor and showed increased SARS-CoV-2 infection as compared to the wildtype ACE2 [9,14,24,26,33,34].…”
Section: Discussionmentioning
confidence: 65%
“…In the current study, p.Lys26Arg was predicted as a benign variant using VarCards in silico analysis tool. Consistently, this variant has been previously classi ed as a benign variant using various in silico analysis tools including SIFT, MUTTASTER, PROVEAN, PolyPhen-2, CADD, and REVEL [24,32,33]. Other studies, based on structural modeling and molecular docking simulations suggested that the p.Lys26Arg increased binding a nity of SARS-CoV-2 spike protein to the ACE2 receptor and showed increased SARS-CoV-2 infection as compared to the wildtype ACE2 [9,14,24,26,34,35].…”
Section: Discussionmentioning
confidence: 66%
“…HEK293T and HeLa cells were cultured in Dulbecco's Modified Eagle Medium (Gibco) supplemented with 10% fetal bovine serum (Gibco), and antibiotic-antimycotic (Gibco) at 37 °C and 5% CO 2 as recently described (Badawi et al, 2022). Cells were grown in 6-well and 24-well tissue culture plates.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%